2003
DOI: 10.1177/00222194030360040201
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Screening Measure for the Identification of Visuospatial Learning Disability in Schools

Abstract: Verbal and nonverbal forms of developmental learning disabilities have been reported. Whereas there are several instruments for evaluating children for the presence of verbal learning disabilities at school, no screening tool is available to identify children who have nonverbal learning disabilities. This study aimed at devising and validating a short screening questionnaire that can be used by teachers in primary schools to identify those children who need to be referred for clinical services because they hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…The phonological deficits group's pattern of scores was typical of individuals with phonological dyslexia (Von Károlyi, Winner, Gray, & Sherman, 2003;Wilson & Lesaux, 2001), and the majority of group members had been so diagnosed. The organizational deficits group pattern was typical of nonverbal LD (Cornoldi et al, 2003), and again, most group members had the diagnosis confirmed as adults. There was no predominant diagnostic status in the mixed deficits group.…”
Section: Fig 1 Linear Relationship Between Gestalt Formation and Reamentioning
confidence: 80%
See 2 more Smart Citations
“…The phonological deficits group's pattern of scores was typical of individuals with phonological dyslexia (Von Károlyi, Winner, Gray, & Sherman, 2003;Wilson & Lesaux, 2001), and the majority of group members had been so diagnosed. The organizational deficits group pattern was typical of nonverbal LD (Cornoldi et al, 2003), and again, most group members had the diagnosis confirmed as adults. There was no predominant diagnostic status in the mixed deficits group.…”
Section: Fig 1 Linear Relationship Between Gestalt Formation and Reamentioning
confidence: 80%
“…In an independent study, there was no difference between Block Design's reliability with a group of adults with cognitive disabilities and reliability coefficients reported in the technical manual for typical adults (Zhu, Tulsky, Price, & Chen, 2001). Block Design has been used extensively and successfully to differentiate research participants with nonverbal LD from those with dyslexia, and those without cognitive disorders (Cornoldi et al, 2003;Pelletier et al, 2001). Kaufman, 1994) is a visual perceptual test of the relational property of closure, or the tendency to perceive full and meaningful forms from incomplete information (Kimchi, 1992).…”
Section: Block Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Appendix A1 presents demographic and selection data for VSLD children. The VSLD children were identified as poor learners on the basis of school reports and difficulties described by their teachers through the Shortened Visuo-spatial Questionnaire (SVS; Cornoldi, Venneri, Marconato, Molin, & Montinari, 2003). The SVS Questionnaire offers a visuospatial score (VS score) based on 10 items (range 10 -40).…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…To do so, fourth-grade children were recruited to participate in the study. They were first required to perform three visuospatial tasks: the NEPSY design copying test (Korkman, Kirk, & Kemp, 1998), the Rey Complex Figure Test (Osterrieth, 1944), and the Cornoldi shortened visuospatial questionnaire (Cornoldi, Venneri, Marconato, Molin, & Montinari, 2003). These three measures were chosen because they are quick, reliable, and valid instruments to identify low visuospatial abilities in primary school.…”
Section: Introductionmentioning
confidence: 99%